Enhancing Professionalism in Academic Agricultural Communications Programs: The Role of Accreditation - Mark Tucker; Sherrie R. Whaley; Larry Whiting; Robert Agunga (Journal of Applied Communications, 2002)
Enhancing professionalism in agricultural and applied communications has been an important topic of discussion among ACE members in recent years. Developing strategies to increase prestige and recognition of this specialized field are of particular interest to ACE members involved in administering academic programs in agricultural communications and agricultural journalism. One of the measures under consideration to bolster recognition is the development of accreditation standards and procedures that would allow for “certification” of academic programs. Among the often-cited advantages of accreditation are increased uniformity of curricula and the development of formal quality- control mechanisms. However, if accreditation standards and procedures are to be implemented successfully, more information is needed on the overall accreditation process, how it has been used in other disciplines, and what factors should be considered in applying it to agricultural communications. This paper attempts to fill this void by providing an overview of the accreditation process and a review of the accreditation literature to identify important issues in developing and implementing such programs. In addition, results from an electronic mail survey of academic agricultural communications program faculty are provided to document their perceptions of the need and role of accreditation in this field. The authors argue that development of a structured accreditation process is not in the best interest of agricultural communications at this time. The paper concludes with a set of discussion items and recommendations for agricultural communications faculty to consider in weighing for themselves the merits of national accreditation standards.